Pengaruh Profitabilitas, Financial Leverage, Dividen, Ukuran Perusahaan, Kepemilikan Institusional, Dan Kelompok Usaha Terhadap Perataan Laba Studi Kasus Pada Perusahaan Non-Finansial Yang Terdaftar Di Bei - Eko Budi Santoso; Sherly Novia Salim (Conference In Business, Accounting, And Management (CBAM), 2012)
This research is designed to examine factors that can be identified with the incidence of income smoothing practice among listed non-financial companies at Indonesian Stock Exchange. Those factors were profitability, financial leverage, dividend, size, institutional ownership, and industry sector. Tucker and Zarowin model is used to determine the income smoothing practices. This research used 89 non-financial companies listed on Indonesian Stock Exchange during a period 2009 – 2010. The hypotheses were tested using multiple regression analysis to examine the influence of these variables to income smoothing. The result of this research showed that profitability and industry sector did not have significant influence to income smoothing. Financial leverage and dividend have negative influence to income smoothing. Size and institutional ownership have positive influence to income smoothing.Keywords: financial leverage, dividend, industry sector, income smoothing.